2007
DOI: 10.1097/mca.0b013e32801104d4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of monocyte and lymphocyte adhesion molecules is increased in isolated coronary artery ectasia

Abstract: Increased levels of cellular adhesion molecules in patients with coronary artery ectasia may be an indicator of endothelial activation and inflammation and are likely to be in the causal pathway leading to coronary artery ectasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Compared to patients with CAD, higher levels of Creactive protein (CRP) (9), adhesion molecules (27,28), leukocytes (29), metalloproteinase-3 (MMP-3) (30), plasminogen activator inhibitor-1 (31) and phospholipase A2 (32) have been reported in patients with CAE. Studies using epicardial fat, obtained during coronary artery bypass surgery, revealed a significantly higher expression of interleukin-1, interleukin-6, and tumor necrosis factor in epicardial fat than those in leg subcutaneous adipose tissue (16,33).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients with CAD, higher levels of Creactive protein (CRP) (9), adhesion molecules (27,28), leukocytes (29), metalloproteinase-3 (MMP-3) (30), plasminogen activator inhibitor-1 (31) and phospholipase A2 (32) have been reported in patients with CAE. Studies using epicardial fat, obtained during coronary artery bypass surgery, revealed a significantly higher expression of interleukin-1, interleukin-6, and tumor necrosis factor in epicardial fat than those in leg subcutaneous adipose tissue (16,33).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the expressions of cellular adhesion molecules including monocytes in patients with CAE are higher than controls [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…57 Elevated cellular adhesion molecule levels in CAE patients may be an indicator of endothelial activation and inflammatory processes. 27 The neutrophil-lymphocyte ratio was significantly higher in the CAE group compared with control, and this ratio was also positively correlated with the number of ectatic segments. 58,59 Furthermore, CAE patients had higher mean platelet and eosinophil volumes.…”
mentioning
confidence: 87%
“…). Additionally, there were 5 articles that studied expression of activation markers in peripheral blood 13,26,27 and expression of ACE genotypes. 28,29 Where methods used to test for plasma biomarkers were reported, enzyme-linked immunosorbent assay was used in 20 groups of patients (71.4%), immunonephelometry in 4 (14.3%), florescence polarization immunoassay (FPIA) in 2 (7.1%) and particle enhanced turbidimetric assay (for hsCRP) and sequential immunometric assay (for IL-6) were each used in 1 (3.6%) patient group (c 2 =59.196, p<0.0001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation